Non-Emptiness, Relative Coincidences and Axiomatic Results for the Precore - Yan-An Hwang; Yu-Hsien Liao (Mathematics, 2023)
Taking into account the definition of the precore, we initially analyze its non-emptiness using duality results from linear programming theory. We then introduce the dominance core to investigate the coincident relations between the precore and dominance core. Finally, we propose specific reduction approaches to axiomatize the precore.